1988
DOI: 10.1200/jco.1988.6.3.509
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic and surgical induction of pathological complete remission and whole abdominal irradiation for consolidation does not enhance the cure of stage III ovarian carcinoma.

Abstract: Thirty-eight patients with stage III ovarian carcinoma were treated with a protocol consisting of an initial phase of induction of remission with cyclophosphamide, hexamethylmelamine, doxorubicin, and cisplatin (CHAD) combination chemotherapy and a second laparotomy for resection of residual tumors, followed by a consolidation phase with curative doses of whole abdominal radiation. Six patients (16%) had stage IIIA disease, ten (26%) IIIB, and 22 (58%) had stage IIIC disease. All patients received three to 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…No comparison was made to an untreated control group. Fuks et al [38] reported no advantage to whole abdominal radiation in 25 patients with negative findings at SLL.…”
Section: Consolidation Therapy After Negative Sllmentioning
confidence: 98%
“…No comparison was made to an untreated control group. Fuks et al [38] reported no advantage to whole abdominal radiation in 25 patients with negative findings at SLL.…”
Section: Consolidation Therapy After Negative Sllmentioning
confidence: 98%
“…Consolidation radiotherapy has been evaluated in a number of reports during the past decade (5,(10)(11)(12)14,(26)(27)(28)(29)(30)(31)(32)(33) . Negative outcomes are reported in a number of these studies (5,(26)(27)(28)31,33) .…”
Section: Discussionmentioning
confidence: 99%
“…Negative outcomes are reported in a number of these studies (5,(26)(27)(28)31,33) . More promising results are presented by others (10)(11)(12)14,29,30,32) , even though most series are small and not randomized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations